2009
DOI: 10.1144/sp312.13
|View full text |Cite
|
Sign up to set email alerts
|

The Cimmerian evolution of the Nakhlak–Anarak area, Central Iran, and its bearing for the reconstruction of the history of the Eurasian margin

Abstract: New structural, sedimentological, petrological and palaeomagnetic data collected in the region of Nakhlak-Anarak provide important constraints on the Cimmerian evolution of Central Iran. The Olenekian-Upper Ladinian succession of Nakhlak was deposited in a forearc setting, and records the exhumation and erosion of an orogenic wedge, possibly located in the present-day Anarak region. The Triassic succession was deformed after Ladinian times and shows south-vergent folds and thrusts unconformably covered by Uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 53 publications
0
116
0
Order By: Relevance
“…According to recent paleogeographic reconstructions proposed by Angiolini et al (2007) and by Muttoni et al (2009aMuttoni et al ( , 2009b, the Iranian plate was rifted apart from Gondwana and began its northward drift during the end of the Lower Permian, colliding with southern Eurasia in the Late Triassic giving rise to the Cimmerian orogenic event (Sengör, 1979(Sengör, , 1984Zanchi et al, 2009aZanchi et al, , 2009b. On the base of our data and previous considerations, we suggest that the Fariman and the Darreh Anjir complexes of NE-Iran were part of the southern Eurasia (Turan plate) active margin, developed in the upper plate of the north to northeast directed Palaeotethys subduction zone.…”
Section: Tectonic Setting Of the Ne Iran "Ophiolites"mentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent paleogeographic reconstructions proposed by Angiolini et al (2007) and by Muttoni et al (2009aMuttoni et al ( , 2009b, the Iranian plate was rifted apart from Gondwana and began its northward drift during the end of the Lower Permian, colliding with southern Eurasia in the Late Triassic giving rise to the Cimmerian orogenic event (Sengör, 1979(Sengör, , 1984Zanchi et al, 2009aZanchi et al, , 2009b. On the base of our data and previous considerations, we suggest that the Fariman and the Darreh Anjir complexes of NE-Iran were part of the southern Eurasia (Turan plate) active margin, developed in the upper plate of the north to northeast directed Palaeotethys subduction zone.…”
Section: Tectonic Setting Of the Ne Iran "Ophiolites"mentioning
confidence: 99%
“…In N Iran, the position of the Palaeotethys suture zone between the Eurasian margin and the Iran block, has been inferred based on the occurrence of thin strips of serpentinites and mafic-ultramafic complexes (Shanderman complex, Gorgan area) interpreted as remnants of the Palaeotethys ocean floor (Davies et al, 1972;Stocklin, 1974;Sengör, 1990;Alavi, 1996). Recent investigations Zanchi et al, 2009aZanchi et al, , 2009b have demonstrated the occurrence of an important orogenic event although the occurrence of remnants of the Palaeotethys ocean in the Alborz chain is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The Alam consists of finegrained volcanic arenite, nodular limestone, and marl with turbidites at the base and intercalations of fluvial conglomerate that become more numerous upward (Zanchi et al, 2009;Balini et al, 2009). The…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2); well south of the main strand of the suture in the Alborz and Kopet Dagh mountains (Bagheri and Stampfli, 2008). Carboniferous accretion (Variscan) at the northern margin of Palaeo-Tethys, prior to the collision within the Yazd Block, has been determined from radiometric ages on metamorphic rocks (Bagheri and Stampfli, 2008;Zanchi et al, 2009Zanchi et al, , 2015. Palaeomagnetic data show that the various blocks of Central Iran have undergone considerable counter-clockwise rotations in the Late Jurassic and Neogene so that their present-day configuration differed considerably to that in the Palaeozoic and early Mesozoic (Mattei et al, 2012(Mattei et al, , 2015.…”
Section: Zagros Orogen and The Cimmerian Continental Fragmentmentioning
confidence: 99%
“…Data from Central Iran, including radiometric ages and mapping of a Variscan suture in the Anarak-Jandaq block, indicate that this block may have been connected with the Palaeo-Tethyan suture in northeast Iran (Bagheri and Stampfli, 2008;Zanchi et al, 2009Zanchi et al, , 2015. Palaeomagnetic data from Central Iran indicate substantial counter-clockwise rotations of the Lut, Tabas and Yazd blocks in the Late Jurassic and Neogene (Mattei et al, 2012(Mattei et al, , 2015, and thus requires substantial changes to the Jurassic and older palaeogeography (Fig.…”
Section: Cimmerian Orogenymentioning
confidence: 99%